Happiness and Burnout Syndrome in health professionals of a National Hospital of Metropolitan Lima in times of pandemic - Collan Velazco, Flor De Los Ángeles Cristina (2023)
The objective of this study was to determine the relationship between happiness and burnout syndrome in health professionals in a national hospital in Metropolitan Lima during a pandemic. For this purpose, a sample of 102 health professionals from a National Hospital located in Metropolitan Lima was used. Likewise, the research was developed under a basic research type, with a non-experimental, cross-sectional and correlational design. The Lima Happiness Scale (EFL) and the Maslach Burnout Inventory (MBI) were used as instruments. According to the results, it was identified that there is a relationship between happiness and personal fulfillment (rs = .277**; p<.05), personal fulfillment in women (rs = .293**; p<.05), emotional exhaustion in married people (rs= -.316; p<.05) and personal fulfillment in nurses (rs = .367**; p<.05). Also, the levels with the highest predominance of happiness were the medium and low levels with 25.49% each. Finally, in relation to burnout syndrome, a low level (48.04%) was evidenced in the emotional exhaustion dimension, a low level (50.98%) in the depersonalization dimension and a high level (58.82%) in the self-fulfillment dimension. In conclusion, there is a relationship between happiness and burnout syndrome.